Special education policy: considerations on target audience, teacher training and funding - Manzini, Eduardo José (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2018)
In this paper, we discuss the political and financial implications in the relationships between the target audience of special education and teacher training. The target audience of special education was restricted by the special education policy. Several actions could be carried out: creation of Multifunctional Resources Classes Rooms, teacher training, financing of the Special Education Support Project. Currently, a new discussion tries to alter this clientele. However, two controversies are present: the first is that the definition of the population served does not seem to frame into categories of disability determined by scientific criteria; the second, when expanding the target audience, financial resources must be expanded. Unfortunately, the country's economic moment does not guarantee the financial contribution to achieve this change. Some municipalities are already outsourcing the Specialized Educational Service to non-governmental institutions. This fact is contributing to the fact that no financial investments are made in the public school, which may become fragile in coming years.